The Ideology of the Republic of Indonesia in an Islamic Political Order - Sutomo; Sutoyo; Vicki Dwi Purnomo (Formosa Journal of Applied Sciences, 2023)
On condition moment This important knowing the State Ideology of Indonesia, namely Pancasila which plays a role in strengthening the existence of this nation. At first glance, this political system seems to rule out aspirations people Islam. Because in country Which majority its inhabitants people Islam, No in a manner firm accommodate law Islam in system political And the law. In this study the authors carry out the normative. Need a writer put forward suggestion as continuation from study writer about things the above so as to be able to provide more complete and concrete information. With the understanding that the position of Pancasila ideology can be recognized as final base And ideology country Which accepted as aspirations people Islam in journey of the formation of Indonesia.